DEVELOPMENT OF TECHNOLOGY OF FUNCTIONAL MAYONNAISE SAUCES - ANTONENKO, АRTEM; BAL-PRYLYPKO, LARYSA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The work presents the development of a technology for functional mayonnaise sauces using gum arabic and hydrated soy phospholipids as emulsifiers, which made it possible to completely eliminate egg powder, reducing the cholesterol content. The study covered the creation of two types of mayonnaise: medium-calorie "Mayonnaise-1" (40% fat) and high-calorie "Mayonnaise-2" (65% fat) with a balanced fatty acid composition due to a combination of peanut, sunflower and soybean oils rich in ω-3 and ω-6 acids. To compensate for the decrease in fat content, gum arabic, eggplant powder and inulin were added to "Mayonnaise-1", which imitates the texture of fat and contributes to the normalization of carbohydrate and lipid metabolism, which makes them promising for dietary nutrition. The recipes "Mayonnaise-3" and "Mayonnaise-4" with water extract of Jerusalem artichoke (inulin content 16.11–19.2%) were also developed, which reduced the calorie content (55.85–60.8% fat) without losing functionality. Organoleptic indicators confirmed a pleasant taste (slightly spicy, sour with a slight mustard aftertaste) and a homogeneous creamy consistency, and physicochemical indicators confirmed high emulsion stability (96–98%) and acidity within the normal range (≤1%). Reducing the oil content led to an increase in the proportion of water (up to 51.85% in "Mayonnaise-1"), while inulin partially compensated for the fat, preserving the texture. "Mayonnaise-2" has a balanced fatty acid composition, which increases its nutritional value. The introduction of gum arabic, eggplant powder and inulin contributes to the normalization of carbohydrate and lipid metabolism, making the sauces suitable for dietary nutrition, in particular for people with metabolic syndrome. The results indicate the possibility of creating functional mayonnaises with improved characteristics for healthy nutrition, in particular for people with metabolic disorders. The studies confirm the prospects of using gum arabic, eggplant powder and inulin as key components in the technology of producing dietary sauces.
Keywords: sauces; mayonnaise; plant hydrocolloids; gum arabic; eggplant powder; dietary fiber; quality; functional product; nutritional value; technology